A Literature Review on the Nexus of Exclusive Breastfeeding and Stunting - Dewi Anjani Mandati; Apoina Kartini; Syamsulhuda Budi Musthofa (Postgraduate, University of Mataram, 2023)
Stunting is a serious nutritional problem faced by almost all developing countries, including Indonesia. Exclusive breastfeeding is one of the factors that influence the incidence of stunting. Infants who do not receive exclusive breastfeeding are more likely to experience stunting, which will cause children to become easily ill, and it is feared that later it will cause impaired productivity after adulthood. This article review aims to understand more about the relationship between exclusive breastfeeding and stunting. The search for scientific articles was conducted through electronic databases such as Science Direct, Scopus and PubMed and 4 articles published in the last 5 years (2018-2013) were selected. The study results from the 4 articles on average informed that exclusive breastfeeding is associated with stunting. In the reviewed articles, mothers who received nutrition counseling may be effective in reducing childhood stunting accompanied by improved feeding practices. To overcome this nutritional problem, the Indonesian government created a program called Keluarga Sadar Gizi (Kadarzi) and Puskesmas is one of the institutions that plays an important role in accelerating efforts to reduce stunting. This study concluded that there is an association between exclusive breastfeeding and stunting